ANALYSIS OF STUDENT NUMERACY LITERACY IN SOLVING PISA QUESTIONS - Sopamena, Patma; Rahmawati, Intan; Lessy, Djaffar; Ma'aruf, Salmiati (IAIN Ambon, 2023)
This study aims to describe the process of student numeracy literacy in solving PISA questions. This study used a qualitative descriptive approach. The subjects in the study were two people from 34 students of 9th grade B MTs N Ambon as participants, with data acquisition including observations, interviews, and numeracy literacy ability tests from PISA questions. Data analysis techniques use data classification, data reduction, data presentation, data interpretation, and conclusions. The results of this study show that: 1) both students have the ability of the main competencies in numeracy literacy, namely capable; of communicating problems, making mathematical models, making representations, arguing and giving appropriate reasons in accountability for their work, making good and correct solving strategies, use formal language, symbol language and technical language and use mathematical tools to facilitate their work. 2) There are differences in the solution of the two students, namely in solving problem number one, there are students who make mathematical modeling with the basic formula of comparison and there are students who make mathematical modeling with the opposite of the basic formula of comparison, namely multiplication.